Why the beach occupancy plan? Different perspectives on coastal development in Tunisia - Dhaher, Najem; Hagui, Abdelhamid (Boletín de la Real Sociedad Geográfica; Núm. CLVIII (2022), 2022)
How can be broadened the scope of concepts for the study of occupation of beaches in Tunisia resulting from the most often illegal comprehensive use of its fragile spaces. Re?ecting on the way to approach bop execution, we are faced with an approach that uses the lessons learned from previous failures to shape a new model based on a purely participatory approach. RESUMEN ¿Cómo se puede ampliar el alcance de los conceptos para el estudio de la ocupa ción de playas en Túnez como consecuencia de un uso ilegal e intensivo de esos frágiles espacios? La re?exión sobre la forma de abordar la ejecución de los Planes Ocupación de Playas (BOP), nos conduce a un enfoque que utiliza las lecciones aprendidas de errores anteriores para dar forma a un nuevo modelo de gestión basado en un tratamiento básicamente participativo.